Social perception and just world belief. A study with Argentinean student - Zubieta, Elena (2006)
In the framework of social perception and attribution theories, fundamental bias of Just World Beliefs developed by Lerner (1965) states that people need to see world as a just place in order to cope with an ordered and controlled sociophysical environment. By holding this ideas people can involve in long term proposes as in daily life social regulated behavior. Pursuing the isolation of a “cognitive invariant”, Just World Beliefs (JWB) thesis can be seeing as dealing with a natural aspect of human being not conditioned by social, cultural or ideological factors. In the need of recovering social dimension of attribution processes, pre- sent study aimed to examine the relationship between Just Word Beliefs (Rubin & Peplau, 1973) and some social variables. A descriptive correlation study was carried out based on a convenience sample of 349 students from Buenos Aires city. As hypothesized, means on JWB increase with age, educational levels, parental education and cultural capital. Similarto previous researches, no differences related to sex were found.